Spasmodic dysphonia: Acoustic measures - Sigal, Liliana (Revista de Investigación en Logopedia, 2013)
Spasmodic dysphonia is a severe voice disorder characterized by involuntary disruption of phonation, also called focal laryngeal dystonia. This study presents the results of an investigation into the acousticvocal characteristics of a population of patients with spasmodic dysphonia, and comparing them with those of a control group (patients with diagnosis of mobile vocal cords, without damage in the structure of the glottal mucosa or neurological disorders involving the movement of the vocal cords). The following parameters were investigated in the emission of the vowel /a /: mean pitch value, standard deviation, minimum pitch, maximum pitch and a number of phonatory breaks. The Praat acoustic analysis system was used for these measurements (Boersma and Weenink, 2003). Regarding results, no significant differences were found between patients and control group for the average measures of mean pitch in both sexes. Comparison of the standard deviation of mean pitch and the ranges between maximum and minimum pitch revealed significant differences between the group of patients and controls. The voice breaks were calculated only in the group of patients. No person in the control group had phonatory disruptions in the emission of the vowel. The standard deviation of mean pitch, the range between maximum and minimum pitch and the number of phonatory breaks during prolonged vowel can be used as indicators of spasmodic dysphonia.
Keywords: Acoustic measures; Laryngeal dystonia; Spasmodic dysphonia; Voice.